Pengaruh Penyuluhan Menggunakan Media Permainan Congklak terhadap Pengetahuan Kesehatan Gigi dan Mulut pada Siswa Kelas IV, V, dan VI SDN Sungai Batang 2 Kabupaten Banjar - Ida Yanti, Nurvania Agitha; Kisworo Utami, Naning; Isnawati, Isnawati; Danan, Danan (JURNAL TERAPIS GIGI DAN MULUT, 2025)
The first step to improve knowledge and preventive measures for dental and oral health complaints in children is to provide dental and oral health counseling or education. Conducting dental and oral health counseling for elementary school children is important, because during this period children will develop habits that often persist into adulthood, one example is the habit of maintaining dental and oral hygiene. The study aims to determine the effect of congklak game media counseling on dental and oral health knowledge in grade IV, V, and VI students of Sungai Batang Elementary School 2, Banjar Regency. The type of research is analytical research with quasi-experimental design (like an experiment). Research samples using techniques total sampling, where all students in grades IV, V, and VI student of Sungai Batang Elementary School 2 total 50 children. The results showed that knowledge of dental and oral health before counseling using the congklak game media was 11.12 and after counseling was 16.20. The test results Paired Sample T- Test in the congklak game media, the value is obtained p = 0.000, so it is smaller than α = 0.05 then H0 rejected and Ha accepted. In conclusion, there is an influence of counseling with congklak game media on dental and oral health knowledge in grade IV, V, and VI students of Sungai Batang Elementary School 2, Banjar Regency. It is recommended that health promotion activities can use congklak game media because it is effective for promotive efforts and school dental health unit.